The implementation of a nursing student clinical assessment tool onto an online platform: An evaluation by clinical facilitators and academic staff. Issue 4 (August 2019) - Needham, Judith; Sidwell, Danny; Frommolt, Valda; Barnewall, Kate; Grafton, Eileen
Abstract: Background: Formative and summative assessment plays an integral role in the learning process for undergraduate nursing students on clinical placement. Aim: Evaluate the integration and implementation of the Australian Nursing standards assessment tool to the online SONIA database. Methods: The study was designed to evaluate the experiences of clinical facilitators and academic staff using the online platform, which included an online survey and focus group sessions. Findings: Whilst there are benefits gained from using the online system, results highlighted limitations in using technological devices on clinical placement and a lack of education in using the online platform. Discussion: Implementation of a student clinical assessment tool onto an online platform was introduced to counteract the inherent challenges of managing hard-copy assessment data and meet sustainable teaching practices. Participants noted an ease of accessibility to assessment, although issues identified were access to internet in healthcare organisations and lack of education prior to the implementation of the online tool would have supported their experience. Conclusion: Integration of the Australian Nursing Standards Assessment Tool (ANSAT) onto the planet software database brought significant improvements to the access and management of clinical placement assessment information.